Demand and technology contribution to structural change and tertiarisation: An input-output structural decomposition analysis - Maria Savona; André Lorentz (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2006)
The paper provides fresh empirical evidence on the relative role of changes in final and intermediate demand as affecting the changes in the sectoral structure of advanced economies. These latter have led, over the last three decades, to the massive growth of service sectors. The paper draws upon the recently released OECD Input-Output (I-O) tables. The empirical analysis is based on an I-O Structural Decomposition Analysis carried out on 13 manufacturing and service sectors, from the end of 1960s to the end of 1990s. Although heterogeneous sectoral patterns emerge, we find that the structural changes leading to the growth of services, particularly KIBS (Knowledge Intensive Business Services), are mainly (domestic) demand-led, whereas the role of foreign trade remains marginal even in the last decade. We infer that, even in the case of the most technologically advanced service sectors, (domestic) demand constraints affect the degree of exploitation of technological opportunities and the patterns of growth.
Keywords: L16; L80; O14; O33; 330; Structural change; Growth of Services; Input-Output Structural Decomposition Analysis; Input-Output-Analyse; Dekompositionsverfahren; Strukturwandel; OECD-Staaten